Interleukin-6 and Interferon-α Signaling via JAK1–STAT Differentially Regulate Oncolytic versus Cytoprotective Antiviral States - Danziger, Oded; Pupko, Tal; Bacharach, Eran; Ehrlich, Marcelo (Frontiers in Immunology, 2018)
Malignancy-induced alterations to cytokine signaling in tumor cells differentially regulate their interactions with the immune system and oncolytic viruses. The abundance of inflammatory cytokines in the tumor microenvironment suggests that such signaling plays key roles in tumor-development and therapy efficacy. The JAK-STAT axis transduces signals of IL-6 and interferons, mediates antiviral responses and is frequently altered in prostate cancers (PCa). However, how activation of JAK-STAT signaling with different cytokines regulates interactions between oncolytic viruses and PCa cells is not known. Here, we employ LNCaP PCa cells, expressing (or not) JAK1, activated (or not) with interferons (IFNs; α or γ) or interleukin-6 (IL-6), and infected with RNA viruses of different oncolytic potential (EHDV-TAU, hMPV-GFP or HIV-GFP) to address this matter. We show that in JAK1-expressing cells, IL-6 sensitized PCa cells to virally-induced cell death in presence or absence of productive infection, with dependence on virus employed. Contrastingly, IFNα induced a cytoprotective antiviral state. Biochemical and genetic (knockout) analyses revealed dependency of antiviral state or cytoprotection on STAT1 or STAT2 activation, respectively. In IL-6 treated cells, STAT3 expression was required for anti-proliferative signaling. Quantitative proteomics (SILAC) revealed a core repertoire of antiviral IFN-stimulated genes, induced by IL-6 or IFNs. Oncolysis in absence of productive infection, induced by IL-6, correlated with reduction in regulators of cell cycle and metabolism. These results call for matching the viral features of the oncolytic agent, the malignancy-induced genetic-epigenetic alterations to JAK/STAT signaling and the cytokine composition of the tumor microenvironment for efficient oncolytic virotherapy.